3D bioprinting of high cell concentrations & cell spheroids to achieve physiologically relevant cell environments - Chua, Cliff Dun An (Nanyang Technological University, 2020)
Cells 3D bio-printed directly into scaffolds are often delivered at low densities. Therefore, it is seen to be desirable to create bio-printed constructs with more physiologically relevant cell densities. The scope of this project aims to cover; the cultivation methods of HEK293T cell spheroids, the optimization of the printability and biocompatibility of alginate hydrogel required for 3D bio-printing of HEK293T spheroids and lastly the assessment of the cell spheroids viability in the shortlisted alginate hydrogel. In the first part of this project, culture methods to form the 293T cell spheroids were studied by investigating how the diameter of each cell-droplet affects the cell spheroids size distribution. The methods used were; hanging drop, 1.5ml microtubes, 96 micro u-well base plate and the micro mould. These methods were cultured for 3 days with a cell concentration of 1000cells/μl and the micro mould method was observed to produce the most consistent cell spheroid size distribution amongst the other 3 methods. The bioprinter used in this project was a pneumatic operated printer. The printability parameters that were investigated were the needle geometry and alginate concentration. The needle size that was found most suitable for the printing process was the 22G tapered needle due to the size of the spheroids which is discussed further in the latter of this report. On the other hand, printing pressure and printing speed were kept at a constant of 0.1MPa and 12mm/s respectively. The constructs 3D printed were single layer prints of four 20mm x 20mm boxes joined together to form a 40mm x 40mm box to mimic a scaffold. Alginate precursors of different concentrations (3 wt. %, 5 wt. %, 7 wt. % & 9 wt. %) were prepared as bio inks to observe their viscosity, resolution and structural integrity during 3D printing. Observations showed that 9 wt. % alginate proved the best viscosity, resolution and structural integrity. Lastly, spheroids were embedded in the alginate at a density of 500 spheroids/ml were monitored through cell proliferation and cell viability tests. For the proliferation test, days 1, 3, 5, 7 and 9 were conducted using the Alamar Blue assay while the viability was observed under the microscope. Various combinations and concentrations of crosslinkers (1% CaCl2, 1% CaCl2 + 1% BaCl2 and 1% CaCl2 + 3% BaCl2) were also used to assess the stability of the alginate. Results proved that the spheroids showed signs of growth and that the spheroids seemed to grow a liking to the alginate hydrogel be it the various concentrations of crosslinkers. However, the weaker the crosslinking, the cell proliferation activity seemed to be lower, as the alginate hydrogel hydrolysed overtime and resulted in the loss of cells due to routine pipetting and discarding. On the other hand, when a stronger crosslinker was used (i.e. BaCl2), the stability showed signs of improvement to the structural integrity, lasting longer a longer period. The stability was then further improved with the 1% CaCl2 + 3% BaCl2 and it proved to have the best degree of hydrolysis resistance, cell sustainability and the longest cell proliferation activity. Interestingly, as the incubation days went by, those spheroids close to each other started to grow towards each other and form a larger cell aggregate proving that the cell proliferation activity was ongoing. Overall, this project may be applicable for in vitro drug testing with 3D models which mimics the actual cellular ECM instead of 2D models which often produce inaccurate clinical results In addition, it can also be used to further understand the cell-cell and cell-matrix interactions during clinical tests and research in the biomedical industry.